A heat-powered ejector chiller working with low-GWP fluid R1233zd(E) (Part2: Numerical analysis). (January 2021) - Mahmoudian, Jafar; Mazzelli, Federico; Rocchetti, Andrea; Milazzo, Adriano
Abstract: This paper numerically investigates the performance of a high capacity, industrial ejector chiller working with the non-flammable, low GWP refrigerant R1233zd(E). The test procedures adopted to acquire the experimental data are explained in part 1 of this work. Different turbulence models were examined in order to accurately predict the ejector off-design transition and critical pressure. A peculiar difference has been noticed between the numerical results obtained when initializing the CFD simulation from the solution of a case with lower or higher condenser pressure. This difference may partly explain the difficulties in the accurate predictions of the critical conditions reported by this and other works in the literature. A detailed discussion is presented on the nature and possible cause of this phenomenon, which is identified as typical of non-linear fluid dynamics.